2022
DOI: 10.1021/acs.inorgchem.2c00917
|View full text |Cite
|
Sign up to set email alerts
|

Template Synthesis of NPN′ Pincer-type Ligands at Titanium Using an Ambiphilic Phosphide Scaffold

Abstract: Ti-imido complex [TiCl­(N t Bu)­(BIPP)] [1; BIPP = bis­(iminophosphoranyl)­phosphide ligand] reacts with terminal alkynes R–CCH (R = phenyl, isopropenyl, cyclopropyl, and 2-pyridyl) via P–P bond cleavage of the BIPP ligand. The resulting complexes [TiCl­(NPN′)­(NPhPPh2)] (2a–d) contain a pincer-type NPN′ phosphide ligand that incorporates the terminal alkyne and the imido ligand from complex 1. Complexes 2a–d feature two chiral centers (Ti and P) with interdependent absolute configurations; thus, they are for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
0
3
0
1
Order By: Relevance
“…In an attempt to isolate a low-coordinate Ti­(III) pincer complex, halide abstraction on 2 was attempted. In order to achieve this, [(SiEt 3 ) 2 (μ-H)]­[BAr F 4 ] (Ar F = C 6 F 5 ) was usedthis has been used to great effect to abstract halides from particularly strong M–Cl bonds (e.g., lanthanides). Addition of [(SiEt 3 ) 2 (μ-H)]­[BAr F 4 ] to 2 in benzene resulted in the immediate formation of a brown oil, which could be extracted with fluorobenzene as a deep brown-red solution. A structural analysis found that only half an equivalent of chloride had been abstracted and a dimeric species could be isolated in the solid state, [(( tBu PCP)­TiCl) 2 (μ-Cl)]­[BAr F 4 ] ( 3 , Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…In an attempt to isolate a low-coordinate Ti­(III) pincer complex, halide abstraction on 2 was attempted. In order to achieve this, [(SiEt 3 ) 2 (μ-H)]­[BAr F 4 ] (Ar F = C 6 F 5 ) was usedthis has been used to great effect to abstract halides from particularly strong M–Cl bonds (e.g., lanthanides). Addition of [(SiEt 3 ) 2 (μ-H)]­[BAr F 4 ] to 2 in benzene resulted in the immediate formation of a brown oil, which could be extracted with fluorobenzene as a deep brown-red solution. A structural analysis found that only half an equivalent of chloride had been abstracted and a dimeric species could be isolated in the solid state, [(( tBu PCP)­TiCl) 2 (μ-Cl)]­[BAr F 4 ] ( 3 , Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…lanthanides). [26][27][28][29][30][31] Addition of [(SiEt3)2(µ-H)][BAr F 4] to 2 in benzene resulted in the immediate formation of a brown oil, which could be extracted with fluorobenzene as a deep brown-red solution. Structural analysis found that only half an equivalent of chloride had been abstracted and a dimeric species could be isolated in the solid state, [(( tBu PCP)TiCl)2(µ-Cl)][BAr F 4] (3, Scheme 3).…”
Section: Methodsmentioning
confidence: 99%
“…1 H NMR (C6D6): 6.90 (m, 1 H, Arp-H), 6.69 (d, 2 JHH = 5.7 Hz, 1 H, Ar-H), 3.37 (s, 4 H, PCH2), 1.28 (s, 36 H, CCH3). 31…”
Section: Synthesis Of ( Tbu Pcp)ticl3unclassified
See 1 more Smart Citation